Um framework para o gerenciamento de incidentes e requisições de tecnologia da informação no Poder Judiciário do Tocantins - Setúbal, Alice Carla de Sousa (Universidade Federal do Tocantins, 2021)
The implementation of the electronic process in the Judiciary of Tocantins has made the business dependent on Information Technology in order to satisfy its strategic objectives, making Governance and Management of Information and Communication Technology of great importance, and the implementation of information processes is essential. management of IT services, aiming to reduce the interruption of IT services and the negative impact on the organization's business. This work aimed to develop a framework for the management of IT incidents and requests, aiming to improve the governance of information technology in the Judiciary of Tocantins. In order to achieve the objectives of this research, the main norms of the Brazilian Association of Technical Standards focused on the management of IT services and the best IT Governance and Management practices were analyzed: COBIT and ITIL. As tools that make up the framework, artifacts were elaborated that allowed to map, implement and monitor the incident and requisition management process. In order to validate the framework, a practical application was made through a case study focusing on the IT user support area of the Court of Justice of Tocantins. As for the service management method developed, it can be said that it proved to be efficient, since it was possible to map the services provided, with their categories and definition of service levels, and to elaborate and monitor the process of managing incidents and requests for services IT.